The upper Echelon theory: a mixed method study of managing knowledge assets in Malaysian hospitals / Hazlina Hassan, Amrizah Kamaluddin, Norman Mohd Saleh and Noradiva Hamzah - Kamaluddin, Amrizah; Mohd Saleh, Norman; Hamzah, Noradiya (UiTM Press, 2023)
Healthcare services have emerged as one of the most essential factors in a country’s economic growth. The purpose of this study was to provide more insights into why some hospitals do better than others by investigating the influence of leadership styles and the role of knowledge assets handled by hospital top management teams. A mixed method was formed by combining a cross-case research approach with a questionnaire survey. The qualitative technique was used by five private hospitals, and the questionnaire survey was completed by the top management teams in 164 hospitals. The crosscase study research demonstrated that the hospital industry’s knowledge assets are extremely unique, particularly in human capital and relational capital. Surprisingly, the survey discovered that physicians are not often direct employees of hospitals. This results in a one-of-a-kind partnership between the hospital and the physicians. Specifically, this study discovered that knowledge assets only mediate the relationship between transactional and transformational leadership styles and hospital performance, but not passive avoidant leadership styles. The study makes a contribution by being one of the first to investigate, from an Upper Echelon viewpoint, the mediating role of knowledge assets in hospital practice in Malaysia, with the findings useful for hospital administration and regulators.